Pengaruh ownership structure terhadap earnings management - Yie Ke Feliana; Richard Valentino Salim (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study investigates the impact of state ownership, institutional ownership, and managerial ownership on accrual and real earnings management in non-financial sector companies listed on the Indonesia Stock Exchange (IDX) during 2020 and 2021. Methods – The research utilizes a sample of 1,327 firm-year observations, comprising 904 companies for accrual earnings management analysis and 423 companies for real earnings management analysis. Established models are employed to measure earnings management. Findings – The results indicate that state ownership does not significantly affect either accrual or real earnings management. Institutional ownership has a significant positive effect on accrual earnings management but no significant impact on real earnings management. Meanwhile, managerial ownership has no significant effect on accrual earnings management but exerts a significant negative influence on real earnings management. Implications - These findings provide insights for regulators, investors, and corporate governance stakeholders regarding the role of ownership structure in earnings management practices. Policymakers may consider these results when designing regulations to enhance financial reporting transparency. Originality – This study contributes to the literature by examining the distinct effects of different ownership structures on both accrual and real earnings management within the Indonesian market, offering empirical evidence from a recent dataset.